Integrated risk assessment and human health hazards via dietary intake of OCPs from cereal crops cultivated across river chenab - Anam Bajwa; Yumna Sadef; Rabia Nazir; Muhammad Zaheer; Sidra Siddique; Hanan Abdulaziz Alismail; Lalita Ambigai Sivasamugham; Adeel Mahmood (Emerging Contaminants)
The current study aimed to employ integrated risk assessment models to estimate carcinogenic and non-carcinogenic human health risks of organochlorine pesticides (OCPs) from Pakistan. GIS-based geostatistical technique was used to classify OCPs' polluted risk zones using risk indexes. The residual level of ∑OCPs detected in wheat and rice ranged from 1.78 to 12.46 ng g−1 and 4.92–18.19 ng g−1, respectively with the prevalence of DDD, DDE and HCH. The distribution pattern revealed a significantly higher concentration towards downstream region, suggesting industrial and agricultural activities as a pollution source in the area. Single pollution index (SPI) was employed for the identification of pollution zones. The findings of SPI for detected OCPs were found (0.7 < Pi < 1), respectively, depicting minimal pollution at the studied sites. Furthermore, risk assessment results reflected non-cancer risk (>1) for studied ∑OCPs. However, the suggested USEPA value for tolerable carcinogenic risk is < 10−6 (one in a million) which was found higher for DDD, DDE, HCH, CT, and HC in the current study. Consequently, the carcinogenic risk in the study area indicated the need for an assessment, monitoring, and reporting program grounded on laws that can reduce pollution and exposure levels to pesticides in Pakistan for good health and well-being.